Elementary School Counsellor Training: A Developmental, Preventive, and a Remedial Perspective - Allan, John A. B.; Der, Du-Fay (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper describes the elementary school counsellor training program at the University of British Columbia. It outlines the background, philosophy, and selection criteria and then delineates in greater detail the core aspects of the program. To date the course has trained 60 students of whom 85% are currently working as elementary school counsellors. The program focuses on the acquisition of developmental, preventive, and remedial coun- selling skills and on communication, consultation, and coordination. Its strength lies in providing trainees with a broadly based theoretical framework and an in-depth supervision of counselling sessions with individuals, small groups, whole classrooms, parents, and teachers.